EXPLORING THE USE OF IMMERSIVE NARRATIVES FOR SOCIAL AWARENESS: GENDER EQUALITY - Rakel Cogliatti de Souza (2023)
The focus of this study is to explore the potential of immersive narratives to debate social awareness in the context of site-specific immersive theatre. The research deploys a qualitative approach combining arts-based and focus group design methods with storytelling techniques. The aim is to examine how young adults perceive gender bias through immersive storytelling and how this can help their state and commit to social justice and equality.